Acolhimento e adaptação de crianças na educação infantil: reflexões a partir de uma instituição pública de Miracema do Tocantins - Silva, Thatyana Furtado da (Universidade Federal do Tocantins, 2021)
This course completion paper presented to obtain a bachelor's degree in Pedagogy focuses some questions and questions that accompany me since the experiences with the Supervised Curricular Internship aimed at Early Childhood Education (kindergarten and pre-school). The insertion in the schools and the monitoring of the routines of daily activities, mainly in day care centers, aroused my interest in discussing the insertion of the children in an institutional context. Throughout the supervised curricular stage, I verified that the insertion of the children in a space other than the domestic one lacked more attention, planning and monitoring, so that the whole process did not imply in a traumatic rupture of a routine experienced by the little ones. Thus, I defined as my object of study the acceptance and adaptation of children in early childhood education, focusing on the day care centers for receiving, according to Brazilian educational legislation, children between zero and three years and eleven months of age. The development of the study was guided by the following problem: how do kindergartens, when they receive the children at the beginning of the school year, build the process of welcoming and adapting the children? Is there a planning of the professionals involved to deal specifically with this issue? The study is based on the following general objective: to identify how children are welcomed when they enter child care centers and to discuss how this process impacts children's adaptation to institutional routines. Among the specific objectives are: to discuss the concept of reception, contemplating the dimensions of care and education, in the pedagogical work developed by day care centers; to conceptualize work routines and the way in which adaptation can be contemplated; evaluate whether and how the teacher is prepared to deal with the adaptive process of the children in the day care center. To collect the data, we started with the observation of the daily routine of activities and interview with teachers of a public day care center in the municipality of Miracema do Tocantins, TO. As research results it was possible to identify that historical heritages still interfere in the structuring of the routine of activities and the conception of education developed in the day care center, with the presence of assistance practices. Reception and adaptation, although developed in some way, need further study and reflection so that the orientation that underpins these elements is based on the integration between care and education.